Pulmonary alveolar proteinosis and anemia may be associated with poor prognosis in patients with IARS1 variants - Shu-Yuan Li; Yu-Ting Wang; Teng Liu (Orphanet Journal of Rare Diseases)
Abstract Background Growth retardation, impaired intellectual development, hypotonia, and hepatopathy (GRIDHH) is a rare disease caused by compound heterozygous variations in the isoleucyl-tRNA synthetase 1 (IARS1) gene. To date, only a few cases have been reported and there has been no comprehensive analysis of its clinical, pathological, molecular genetic features, or factors associated with a poor prognosis. Methods Three new cases of IARS1 deficiency have been documented. A review and summary of the clinical, pathological, and molecular genetic features of previously reported cases was conducted. The prognostic significance of identified risk factors was evaluated using Kaplan-Meier plotter analysis. Results The 3 new cases harbored 6 novel variants in IARS1. The principal clinical manifestations of IARS1 deficiency were intrauterine growth retardation (13/13), failure to thrive (13/14), feeding difficulties (10/14), elevated aminotransferases (11/14), cholestasis (8/14), acute liver failure (7/14), hepatomegaly (7/14), hypoalbuminemia (10/14), coagulation abnormalities (8/14), microcephaly (11/14), neurodevelopmental delay (10/14), hypotonia (9/14), impaired intellectual development (6/7), recurrent infections (9/14), special facial appearance (8/14), zinc deficiency (4/7), and pulmonary alveolar proteinosis (3/14). The principal pathological features of the liver were fibrosis (6/8), hepatocellular steatosis (5/8), and cholestasis (5/8). A total of 24 variants were identified in 14 cases, comprising a frameshift variant (n = 3), nonsense variant (n = 3), splice variant (n = 2), and missense variant (n = 16). Of the 14 cases, five resulted in death. Kaplan-Meier analysis indicated that the occurrence of pulmonary alveolar proteinosis (HR = 10.837, 95% CI = 1.246–94.257, P = 0.031) and anemia (HR = 15.411, 95%CI = 2.101-113.057, P = 0.007) were associated with a poor prognosis. Conclusions In this report, we present three new cases of IARS1 deficiency and provide a comprehensive summary of the clinical, pathological, and molecular genetic characteristics observed in all previously reported cases. Furthermore, our findings suggest that the presence of pulmonary alveolar proteinosis and anemia may be associated with a poor prognosis.